Study on methane oxydative chlorination process under pressure - Yu. A. Treger; L. I. Trusov; V. N. Rozanov; I. S. Silina; O. P. Murashova; V. Ya. Yaskova; L. G. Bruk (Тонкие химические технологии)
The process of the oxidative chlorination of methane carried out in a flow reactor was investigated in the temperature range of 370–400°C under a pressure of 1–9 ata. The catalyst is a mixture of copper chloride, potassium chloride and lanthanum chloride on a porous support. The molar ratio CuCl2:KCl:LaCl3 is 1:1:0.3. The process was studied in an excess of methane at the reactants ratio CH4:HCl:O2 12:2:1 and 13.5:1:0.5. It was shown experimentally that the productivity of the methane oxychlorination reactor increases proportionally to pressure in the degree ~ 0.85. It was found that an increase in the selectivity of the methane oxychlorination process to the desired product – methyl chloride – (more than 90%) is achieved by increasing the ratio of methane to the sum of hydrogen chloride and oxygen.